Mulheres aprendem com mulheres : diálogo intergeracional sobre a prática de amamentar e os cuidados com o bebê - Martins, Rosa Maria Castilho (Universidade Federal de São Carlos, 2012)
To increase the awareness of breastfeeding practices, one must bear in mind that this is a complex act, permeated by the influence of several factors, including the family members. In order to better understand the family context of pregnant/lactating women and identify what they learn with their mothers and mothers-in-law we developed the following research question: What are the existing educational processes in the dialogue between two generations of women about breastfeeding practices and newborn care practices? The objective of this study was to understand what women of different generations learn and teach about breastfeeding practices and newborn care practices, seeking to reveal the type of support and influence that mothers and mothers-in-law may exert on breastfeeding practices. This was a qualitative study, which had the participation of eight women residing in a low socioeconomic neighborhood, and the following techniques were used for data collection: semi-structured interviews and informal conversations. For data analysis we adopted the assumptions of the hermeneutic-dialectic analysis, which led to the development of categories that enabled us to understand: the diversity of motherhood and breastfeeding experiences, the grandmothers knowledge on breastfeeding, the educational processes in the dialogue between women of different generations and the grandmothers potential for encouraging and supporting breastfeeding. We conclude that grandmothers are reference persons in the family, that they have various forms of knowledge about breastfeeding and about caring for newborn babies and who transmit this knowledge to their daughters and daughters-in-law. Thus, when developing actions to promote, protect and support breastfeeding, health professionals need to acknowledge and value the knowledge that women bring from their own child rearing experiences, in addition to building a dialogical relationship that enables to consider and expand this knowledge, enhancing the role of grandmothers as supporters of breastfeeding.
Keywords: Práticas sociais e processos educativos; Diálogo entre gerações; Amamentação; Mulheres; Bebê - cuidado e higiene; Educational processes; Intergenerational dialogue; Breastfeeding women; Newborn care practices; CIENCIAS HUMANAS::EDUCACAO